Recent Advances in Long-Acting Drug Delivery and Formulations - Adel Al Fatease; Hamdy Abdelkader (MDPI AG, 2023)
Conventional immediate-release delivery systems are simple, industrially reproducible, acceptable, and easy-to-use by most patients [...]